A case study evaluating deep inspiration breath‐hold and intensity‐modulated radiotherapy to minimise long‐term toxicity in a young patient with bulky mediastinal Hodgkin lymphoma. Issue 1 (11th February 2017) - Tomaszewski, Jonathan M.; Crook, Sarah; Wan, Kenneth; Scott, Lucille; Foroudi, Farshad
Abstract: Radiotherapy plays an important role in the treatment of early‐stage Hodgkin lymphoma, but late toxicities such as cardiovascular disease and second malignancy are a major concern. Our aim was to evaluate the potential of deep inspiration breath‐hold (DIBH) and intensity‐modulated radiotherapy (IMRT) to reduce cardiac dose from mediastinal radiotherapy. A 24 year‐old male with early‐stage bulky mediastinal Hodgkin lymphoma received involved‐site radiotherapy as part of a combined modality programme. Simulation was performed in free breathing (FB) and DIBH. The target and organs at risk were contoured on both datasets. Free breathing‐3D conformal (FB‐3DCRT), DIBH‐3DCRT, FB‐IMRT and DIBH‐IMRT were compared with respect to target coverage and doses to organs at risk. A 'butterfly' IMRT technique was used to minimise the low‐dose bath. In our patient, both DIBH (regardless of mode of delivery) and IMRT (in both FB and DIBH) achieved reductions in mean heart dose. DIBH improved all lung parameters. IMRT reduced high dose (V20), but increased low dose (V5) to lung. DIBH‐IMRT was chosen for treatment delivery. Advanced radiotherapy techniques have the potential to further optimise the therapeutic ratio in patients with mediastinal lymphoma. Benefits should be assessed on an individualised basis. Abstract : We have described a patient with early‐stage bulky mediastinal Hodgkin lymphoma, receiving involved‐site radiotherapy as part of combined modality therapy. Using two widely available radiotherapy technologies, we were able to achieve a 20% reduction in mean heart dose while maintaining optimal target coverage. This is the first report in Australasia describing the combined use of deep inspiration breath‐hold and intensity‐modulated radiotherapy for mediastinal lymphoma.